Inhabit in the pandemic: the news published on the ArchDaily website - Paula, Ana Luiza Delgado de; Braida, Frederico (National Journal of City Management, 2021)
This article approaches pandemic’ influence in architecture and urbanism and tries to answer the question: what are the main subjects that have been discussed by architects and urbanists in the news when they try to understand the relationship between habitation and pandemic? The article’s purpose is to reveal an overview of the main reflexions running on specialized websites, such as searches at ArchDaily Brazil, about how Covid-19 affects architecture and urbanism. It’s a qualitative research with an exploratory character and a sistematic literature review with an extensive content analysis. In the end, some topics try to bring possible answers for the distancing and social isolation repercussions in residential architecture and cities.